Silicon based materials for spintronics prepared by implantation and temperature - (pressure) treatment - Misiuk, A.; Ch. Lee (Functional Materials, 2008)
This work reviews the hitherto published and new results concerning the compositional, structural and magnetic properties of single crystal Si irradiated/implanted with non-magnetic atoms and, especially, with medium dosage (D≤1*10¹⁶ cm⁻²) of V⁺, Cr⁺ and Mn⁺, and subsequently processed at HT-(HP). The HT-(HP) treatment affects, among others, the solid phase epitaxial re-growth of amorphous a-Si layer created at implantation. Processed Si:V, Si:Cr and Si:Mn indicate magnetic ordering up to above 300 K. This means that the new Si:V, Si:Cr and Si:Mn materials belonging to the family of Diluted Magnetic Semiconductors have been produced.